2008
DOI: 10.1111/j.1478-3231.2008.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans‐retinoic acid ameliorates carbon tetrachloride‐induced liver fibrosis in mice through modulating cytokine production

Abstract: Our findings indicate that ATRA ameliorates liver fibrosis. As the oral administration of the drug results in good compliance, ATRA could be a novel approach in the treatment of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 25 publications
4
36
1
Order By: Relevance
“…Retinoid receptor signaling in hepatocytes is implicated in liver carcinogenesis, and a synthetic acyclic retinoid, peretinoin, has been assessed as a potential cancer chemoprevention measure [227, 228]. In HSCs, all-trans retinoic acid (ATRA) (an RAR ligand) moderately inhibits expression of procollagen I, III, IV, fibronectin, laminin, αSMA, TGFβ, and IL-6, but with no effect on cell proliferation, whereas 9-cis (RXR ligand) moderately inhibits proliferation without affecting the fibrogenic gene expression in rodents [229, 230]. These receptors, also together with PPARγ signaling, have additive inhibitory effects on HSC activation [231, 232].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Retinoid receptor signaling in hepatocytes is implicated in liver carcinogenesis, and a synthetic acyclic retinoid, peretinoin, has been assessed as a potential cancer chemoprevention measure [227, 228]. In HSCs, all-trans retinoic acid (ATRA) (an RAR ligand) moderately inhibits expression of procollagen I, III, IV, fibronectin, laminin, αSMA, TGFβ, and IL-6, but with no effect on cell proliferation, whereas 9-cis (RXR ligand) moderately inhibits proliferation without affecting the fibrogenic gene expression in rodents [229, 230]. These receptors, also together with PPARγ signaling, have additive inhibitory effects on HSC activation [231, 232].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Several studies have shown that exposure of activated HSCs to retinol [11] , retinyl palmitate [12] , and RA [13,14] inhibited their proliferation, as well as the synthesis of collagen and TGF-β. However, some findings suggested that during the development of liver fibrosis, endogenous RA stimulates the synthesis of plasminogen activator (PA) and induces PA/plasmin-dependent latent TGF-β activation in HSC cultures, culminating in the augmented collagen synthesis, thus promoting fibrogenesis [15][16][17] .…”
Section: Disscussionmentioning
confidence: 99%
“…As for liver function, ATRA has become one of the potential candidates for treatment of liver cirrhosis because it suppresses liver fibrosis through reduction of production of transforming growth factor β 1 (TGF β-1), interleukin 6, and type I collagen (11,12 (15). One of the limitations of bisphosphonate is that this may be influenced by renal dysfunction (15,16).…”
Section: One Of the Most Characteristic Features In The Present Case mentioning
confidence: 99%